V horizon development and factors associated in different geomorphological units of an arid-region alluvial fan. Pre-Andes of San Juan, Argentina. (October 2022) - Ocaña, Raúl Emmanuel; Flores, Daniel Germán; Ribas Fernández, Yanina Antonia; Esper Angillieri, María Yanina
Abstract: Alluvial fans are frequently associated with desert pavements and V horizons. In particular, the Talacasto River alluvial fan presents a spatial configuration that gives rise to different levels of deposition. The present work has the following objectives: 1: determine whether geomorphological and superficial characteristics of the landforms influence the presence, development and spatial distribution of soils and V horizons. Also, if vegetation patterns could be used as indicators of the V horizon, and 2: analyze the relationship between geomorphometric characteristics, soil properties and vegetation patterns in the different geomorphological units. Soil and vegetation studies were performed along the different geomorphological units (9) for the alluvial fan. Soil morphology and physical properties were analyzed, emphasizing the presence of the genetic V horizon. In addition, the surface properties and the attributes of plant communities were quantified. The relationship between soil, geomorphometric and vegetation variables was evaluated through Redundancy Analysis (RDA), Spearman's Correlation Analysis and Generalized Linear Models (GLM). The results show that the V horizon is heterogeneously distributed over the alluvial fan. In the older alluvial levels, the V horizon is thicker and finer-textured compared to modern levels. In addition, the V horizon of geomorphic surfaces is negatively correlated with slope and positively correlated with wind effect. V Horizon thickness is positively correlated with sediment coverage, however, it does not show correlation with the vegetation and rock coverage, while the vegetation and rock coverage present a strong negative correlation. The vegetation patterns show significant differences between geomorphological units analyzed. Species richness and diversity are positively correlated with sediment coverage, but are not correlated with V horizon thickness, therefore, species richness and diversity are not good predictors. Our main conclusion indicates that the presence of the V horizon depends on the geomorphometric properties. In contrast, the thickness of the V horizon is independent of vegetation and rock coverage. Two plant species could be used as predictors of the presence and thickness of the V horizon, L. cuneifolia and B. retama. Highlights: In the older alluvial levels, the V horizon is thicker and finer-textured compared to modern levels. The presence of the V horizon depends on the geomorphometric properties of the geomorphic surfaces. The vegetation patterns analyzed are not good predictors of the V horizon.